Avaliação biogeoquímica dos solos e do medronheiro na área mineira da Panasqueira - Godinho, B. (2010)
Panasqueira mine is one of the most important mines in Portugal. Over the last century exploration of tungsten, copper and tin has contributed to produce many waste materials that constitute tailings with huge dimensions generating high visual and chemical impacts. The objective of this work was to study the biogeochemical impact of mining on the soils and arbutus trees (Arbutus unedo) in this area